Patient and primary care physician perceptions of penicillin allergy testing and subsequent use of penicillin-containing antibiotics: a qualitative study - Wanat, M; Anthierens, S; Butler, CC; Savic, L; Savic, S; Pavitt, SH; Sandoe, JAT; Tonkin-Crine, S (Elsevier, 2019)
Background Removal of an inaccurate penicillin allergy record following testing allows patients to access first-line treatment for infections, and reduce the use of broad-spectrum antibiotics, which contribute to antibiotic resistance. However, it is seldom undertaken.